Peculiarities of the Methodology of Accelerated Learning of English - Ismatovna, Daminova Gulabza (Research Parks Publishing LLC, 2023)
Accelerated English Language Learning provides a comprehensive overview of strategies and approaches that can help students effectively master English in the shortest time possible. It begins with an introduction to the importance of setting goals and developing a learning plan.